The rest of the story - Dessen, Sarah (Balzer + Bray, an imprint of HarperCollinsPublishers, 2019)
Unexpectedly sent to spend the summer with her late mother's estranged relatives at scenic North Lake, a teen finds herself torn between her mother's working-class relatives and her father's wealthier associates.